A school‐based health centre partnership: Faculty practice, nursing student learning and wellness in youth, families and community. Issue 1 (10th February 2022) - Beierwaltes, Patricia; Bell, Sue Ellen; Cornell, Rhonda; Ostrow, Laurel Gail; Schmitz, Nicole; Verchota, Gwen; Clisbee, David; Houston, Rebecca; Eggenberger, Sandra K.
Abstract: Aims and Objectives: This paper describes the development of a SBHC with an innovative model of care that grew out of a partnership between a public‐school district and a university nursing programme in the midwestern region of the United States. Background and Purpose: Persistent barriers to health and health care experienced by youth are well documented. School‐based health centres (SBHCs) can improve educational and health outcomes, positively impacting health equity. Academic systems are positioned to address health care needs of the school‐aged population, yet educators face challenges of accessing quality learning placements for students and faculty practice sites. Methods: A community‐based collaborative methodology guided the planning phases that were driven by priority needs identified by families and stakeholders. With the mission of "partnering with students, families, and communities in the promotion of health and wellness through engagement in practice, education, and research, " an ongoing dialogue over a two‐year period led to articulating a vision, designing a plan and implementing a nurse‐managed SBHC. The Standards for Reporting Qualitative Research (SRQR) checklist was considered in the preparation of this paper. Results: In three years, this SBHC has addressed and identified priority needs and served individual youth and families. The SBHC provides opportunities for the faculty to fulfil a practice requirement for certification and accreditation. Nursing students engage with youth and families in health education and health promotion while strengthening their technical and relational skills. Family nurse practitioner students gain valuable clinical experience. Faculty with expertise in family nursing guide family assessments, support family resiliency and direct therapeutic conversations with family units. Conclusion: SBHCs serve youth, families, and community. This academic–practice partnership has the added benefit of providing faculty practice opportunities and nursing student experiential learning. Relevance to Clinical Practice: SHBCs provide practice opportunities that address needs in individuals, families, and communities. Partnerships should be considered at academic nursing programmes to support their needs and fulfil commitments to address health equity gaps.